Problematyka odpowiedzialności perlokucyjnej w pracy nauczycielskiej - Niećko-Bukowska, Bożena (Investigationes Linguisticae, 2007)
This article is about the relation between axiology and linguistics. This axiolinguistics study focuses on the issue of responsibility for the speech acts. The perlocutive responsiblility is the responsiblility for social facts created by means of acts of speech. The responsiblility is related to the teaching and education in social practice. I have described the development of the notion of responsibility starting from the Roman law up to Heidegger?s ontologisation of the responsibility. I refer to the problem of evaluation of reality by humans, by means of assessments, performatives and norms; to the responsibility for the transmission of values among generations. The idea of perlocutive responsibility is shown on the example of education processes at school.